Help-Seeking Attitudes of United Arab Emirates Students: Examining Loss of Face, Stigma, and Self-Disclosure ψ. (April 2016) - Heath, Patrick J.; Vogel, David L.; Al-Darmaki, Fatima R.
The psychological help-seeking patterns of college students in the United Arab Emirates (UAE) have only recently begun to be examined. Initial suggestions indicate that the majority of Emirati students treat help seeking from counselors as a last resort, which may be linked to aspects of Emirati culture including feared loss of societal face, stigma associated with seeking help, and discouragement of self-disclosure to individuals outside of the family. The relationship among fear of losing face, stigma, self-disclosure expectations (i.e., risks and benefits), and help-seeking attitudes was examined using structural equation modeling with 407 Emirati college students. Loss of face and stigma were related to self-disclosure expectations, which in turn were related to help-seeking attitudes. Gender differences were also examined with results indicating significant mean differences across all variables, as well as across two paths of the structural model. These findings are discussed within the cultural context of the UAE.